Analisis Beban Pencemaran Tambak Udang di Sekitar Sungai Kembung Kecamatan Bantan Bengkalis - Harianja, Ronitua Saut Marito; Anita, Sofia; Mubarak, Mubarak (Universitas Riau, 2018)
Research on pollution load of shrimp ponds around Sungai Kembung in Bengkalis Island Riau Province cultivate shrimp with intensive cultivation technology. Feeding that is not appropriate for size can contribute nitrate and phosphate levels to nature that can trigger eutrophication. The purpose of this research is to analyze the pollution load BOD5, DO, NO3 - dan PO4-3 at Sungai Kembung. The results showed that pollutant concentrations in the River Kembung had crossed the threshold according to KepMen LH No 51/Men-KLH/2004 which is destined for marine biota. The pollution load BOD5 shows that Statiun 2 is the highest station receiving pollution loads equal to 16.094 tons/month. Nitrate pollution load on the Station 2 is the highest station to receive pollution load is equal to 39 tons/month. The pollution load of phosphate indicates that the Station 2 is the highest station to receive pollution load that is equal to 38 tons/month. The pollution load of DO indicates that the smallest contamination load (the most polluted) is on the Station 1 equal to 278 tons/month.